2015 UK National Guideline on the management of non-gonococcal urethritis. (February 2016) - Horner, P; Blee, K; O'Mahony, C; Muir, P; Evans, C; Radcliffe, K
We present the updated British Association for Sexual Health and HIV guideline for the management of non-gonococcal urethritis in men. This document includes a review of the current literature on its aetiology, diagnosis and management. In particular it highlights the emerging evidence that azithromycin 1 g may result in the development of antimicrobial resistance in Mycoplasma genitalium and that neither azithromycin 1 g nor doxycycline 100 mg twice daily for seven days achieves a cure rate of >90% for this micro-organism. Evidence-based diagnostic and management strategies for men presenting with symptoms suggestive of urethritis, those confirmed to have non-gonococcal urethritis and those with persistent symptoms following first-line treatment are detailed.